Construction of Analytical Thinking Skills Instruments for Micro Teaching Courses - Blegur, Jusuf; Mahendra, Agus; Mahardika, I Made Sriundy; Lumba, Andreas J. F.; Rajagukguk, Christin P. M. (Journal of Education Reseach and Evaluation, 2023)
Living the life of the 21st century, one of the essential things that the world of education pays attention to is the development of students' analytical thinking skill activities. Research in various countries found only a few studies on developing analytical thinking instruments for Micro Teaching courses. Reports of several studies are limited to developing analytical thinking instruments for elementary school students. This research aims to construct analytical thinking skill instruments for Micro Teaching courses by adopting a development research model (test design, test trials, and test assembly). Nine items were designed using the concept of analytical thinking skills from Anderson and his colleagues; differentiation, organizing, and attributing, then validated by nine raters and tested on 30 students. Content validity testing (rater assessment) uses the Aiken–V formula, reliability testing uses Cronbach's alpha formula, Inter–Rater Reliability testing from Pearson's Intraclass Correlation Coefficients, construct validity testing uses Exploratory Factor Analysis (EFA), as well as analyzing the difficulty and discrimination item. The research results prove that the validity of the content of each item and the reliability test has been fulfilled. While the results of the trial using EFA confirmed the formation of three dominant factors with a loading factor value of ˃0.50, with a reliability coefficient of 0.82. The instrument is appropriate to use because, in addition to fulfilling the parameters of statistical testing, this instrument is also more operational, contextual, and practical to use to measure and assess analytical thinking skills for Micro Teaching courses.